Bubbles and Experience: An Experiment - Dufwenberg, Martin; Lindqvist, Tobias; Moore, Evan (American Economic Review, 2005)
We investigate the occurrence of bubble-crash pricing patterns in laboratory financial markets with a mixture of experienced and inexperienced traders. We find that even with a minority of experienced traders, bubbles are substantially abated.